Media Pembelajaran Slola Berdasarkan Kitab Sinoptis - Hasudungan Simatupang (International Forum of Researchers and Lecturers, 2024)
This research aims to find out how the Synoptic book views SLOLA learning media. To answer this problem, it is necessary to conduct research using topical methods after exploring information from the Synopsis book which is used to gain knowledge about learning media. The results of this research revealed that Jesus used this media as a learning tool which aimed to concretize abstract things in physical form, namely: symbols, symbols, signs, paintings/drawings and original tools which were able to streamline and activate a series of learning processes. Learning media is a tool used to channel messages or content of learning material that can stimulate thinking, influence the attention of people who are learning so that the learning process can be made more effective. The urgency of SLOLA learning media is very central in order to master a number of learning objectives. For this reason, this media is a learning tool for Christian Religious Education